Health Literacy Advances and Trends - Miguel Rios-González, Carlos (IntechOpen, 2023)
The term "health literacy" was used for the first time in 1974 at a conference on health education and social policy; its definition has evolved over time to encompass both the patient's understanding and their ability to process and interpret the health information they receive. The WHO defines health literacy as "the social and cognitive skills that determine the level of motivation and the ability of a person to access, understand and use information in a way that allows them to promote and maintain good health". Literacy in health not only means that the person understands the information that the health professional gives them or that comes to them but also implies that they know how to identify accurate and appropriate information, how to interpret and judge this information, and are able to apply it according to individual circumstances and needs.